Collide - Bal Khabra (Bloomsbury Publishing London, 2024)
Collide is the first book in the Off the Ice series The second novel, Spiral, is out now and the third, Revolve, will be out in October. You can pre-order Revolve now. 'Equal parts spicy and sweet' Peyton Corinne, author of Unsteady When Summer Preston's professor issues her with an ultimatum, she finds herself on an unexpected collision course with hockey captain Aiden Crawford. Summer hates everything about hockey, for good reason, but she isn't going to let that stand in the way of her becoming a sports psychologist. Aiden loves being the hockey captain, except when his team's reckless mistakes risk jeopardising their entire season. When Coach puts him forward for a research paper as punishment, he has no choice but to accept. Summer can't stand his blase approach to life, and Aiden doesn't understand her uptight, scheduled one. They are off to a rocky start, and provoking each other - it turns out - is what they do best. As sparks fly, neither wants to be the one to give in. Can they get everything they want - including each other? Now with a never-before-seen bonus scene from Summer and Aiden's love story as well as an extract from Spiral, the next book in the Off the Ice series. Find out which of your favourite characters from Collide will be featured next! If you love... Ice hockey College setting Reverse grumpy meets sunshine Forced proximity No third act breakup Multi-racial characters He falls first Dual POV ... you're going to love Collide Readers are falling for Summer and Aiden... 'The spice levels won't disappoint' 'Someone please point me in the direction of where I can get my own Aiden Crawford' 'If you loved The Deal and Icebreaker, you'll love this!!! I could not put this book down!' 'Bal Khabra is quickly becoming one of my favourite sports romance authors!' 'Bal Khabra never disappoints. I will read anything she will write. PERIOD.' Spiral ranked No. 6 in the Sunday Times bestseller chart week ending 01/02/2025.
Keywords: English Fiction